(3GdGYJUGe (B/s - (3GdTGWHj, EHQGgje Hf ehSi Hf eMeO,s (3J(B. 790 (3g`(B.s; (3GdTbjQ, eMeOHf YHO GdQMef,s 1377 (3g`(B-s ((3GdOeGe , GdSYhOjI (B:s (3OGQ GHf GdLhRj,s, 2010)
(3jJfGhd GdcJGH GdHOY hJYQjagG hCKQgG Ydi GdOjf GdESdGej hGdCeI GdESdGejI(B.s
Keywords: (3GdHOY aj GdESdGes